Optimizing Arabic Oral Skills Instruction: Exploring Learner Demographics And Preferred Teaching Methods - Che Mat, Azman Bin; Nokman, Ahmad Zulfadhli; Ramli, Nazratul Aini; Musilehat, Nor Shaifura; Abu Bakar, Ahmad Fakrulazizi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to identify teaching methods and student demographic differences that may contribute to students' achievement in mastering Arabic oral proficiency. The study used two qualitative approaches based on interviews with students involved in teaching Arabic using structured questions. Respondents were selected according to their achievement level based on an evaluation by lecturers who taught them. The quantitative approach is also cross-sectional, using questionnaires to collect data. The sample consisted of first-degree students in UiTM who are taking the subject of Arabic as a third language. A total of 257 students responded to the survey. The findings show that specific teaching methods contribute to Arabithec language students' oral proficiency, while demographic factors also provide significant results. Gender and education experience also have a substantial effect on students learning Arabic. This study suggests that varied teaching methods were applied to teach Arabic as a third language, particularly in UiTM. In teaching and learning languages, especially Arabic as a third language, various teaching methods are used to ensure that students master the required language skills, such as oral skills. Teaching methods should consider demographic factors that contribute to students' oral skills.